In real life - Doctorow, Cory (Square Fish, 2018)
Arizona high school student Anda befriends Raymond, a poor Chinese boy, through a massively multiplayer online game called Coarsegold after she discovers that Raymond is breaking the rules of the game by selling in-game resources to wealthy players to help survive his real-world poverty.